Is bond stretch isomerism in mononuclear transition metal complexes a real issue? The misleading case of the MoCl5/tetrahydropyran reaction system1. Issue 28 (28th July 2015) - Di Nicola, Francesco Paolo; Lanzi, Massimiliano; Marchetti, Fabio; Pampaloni, Guido; Zacchini, Stefano
<x xml:space="preserve">Abstract</x> The MoCl5/tetrahydropyran reaction system provides an opportunity for discussing the possible generation of bond stretch isomers.